Study of the intracellular trafficking of the pre-T-cell receptor and its role in T-cell lineage commitment - Smid, Andrei Iosif (Apollo - University of Cambridge Repository, 2019)
T-cell development is a complex multi-step process, driving the maturation of hematopoietic stem cells into fully functional mature T-cells that play a major role in the adaptive immune response against pathogens. This developmental process is regulated by a series of checkpoints in which the signalling capacity of the T-cell antigen receptor (TCR) is tested. One such checkpoint is the generation of the clonotypic chains of the two TCR variants (αβ-TCR or γδ-TCR) by V(D)J recombination. Importantly, the TCRα chain is rearranged only after correct TCRβ expression, which requires the latter chain to pair with a surrogate invariant pre-Tα chain to form the pre-TCR complex. While both TCR variants activate the same signalling pathway, they commit the T cells to distinct functional lineages. Insight into how thymocytes are nonetheless able to distinguish between these two signals is crucial to our fundamental understanding of T-cell development and how it might be manipulated therapeutically. Pertinently, the pre-TCR is undetectable at the cell surface, unlike the γδ TCR which is primarily located at the plasma membrane. In this thesis, I aim to investigate whether the distinct intracellular localisation of the pre-TCR provides a mean for this signal to be distinguished from that of the γδ-TCR. Through the reconstitution of pre-TCR expression in a non-immune cell, I show that although the pre-TCR can in fact translocate to the cell surface, it is rapidly removed via clathrin-mediated endocytosis and transported to lysosomes. The use of a non-immune cell permits the study of pre-TCR trafficking in the absence of other signalling components and demonstrates that this intracellular localisation of the pre-TCR is intrinsic to the receptor. Using a panel of truncated and engineered pre-TCR, I demonstrate that the absence of a second Ig domain in the extracellular domain of the pre-Tα chain promotes the rapid endocytosis of the receptor. In a thymocyte-OP9-DL1 co-culture system, I show that recombination-deficient thymocytes expressing a pre-TCR variant lacking the TCRβ variable domain is sufficient to drive cells through the TCRβ-selection checkpoint and give rise to double positive cells. Likewise, wild type thymocytes over-expressing the pre-TCR or a receptor with a fused TCRα variable domain may push thymocytes down the γδ-lineage. Finally, I employ a biotin proximity-labelling assay to screen for binding partners of the pre-TCR that might mediate its internalisation. Using this method, I identify TMEM131, a novel protein with an unknown function and characterise some of its biochemical and cell biological properties.
Keywords: T-cell; T-cell development; Pre-T-cell receptor; Trafficking; TCR signalling; γδ-TCR; OP9-DL1 co-culture; hematopoietic stem cells; BioID2